Hyperthermic isolated limb perfusion, preoperative radiotherapy, and surgery (PRS) a new limb saving treatment strategy for locally advanced sarcomas. Issue 7 (26th February 2018) - Stevenson, Marc G.; Seinen, Jojanneke M.; Pras, Elisabeth; Brouwers, Adrienne H.; van Ginkel, Robbert J.; van Leeuwen, Barbara L.; Suurmeijer, Albert J. H.; Been, Lukas B.; Hoekstra, Harald J.
Abstract : Background: This feasibility study presents the results of a new intensive treatment regimen for locally advanced extremity soft tissue sarcomas (ESTS), consisting of hyperthermic isolated limb perfusion (HILP), preoperative external beam radiotherapy (EBRT), and surgical resection. Methods: From 2011 to 2016, 11 high grade locally advanced ESTS patients underwent this treatment regimen. Preoperative EBRT (12 × 3 Gy) started <4 weeks following the HILP (TNF‐α and melphalan) and the surgical resection was planned to take place <2 weeks following the end of the EBRT. Results: All patients completed the treatment. After a median follow‐up of 32 (23‐50) months, the limb was saved in 10 patients (91%), 1 patient (9%) developed a local recurrence, 5 patients (45%) developed distant metastases, and 3 patients (27%) died of their disease. During follow‐up two patients (18%) developed a pathologic fracture of the treated limb and three patients (27%) developed a major wound complication requiring surgical intervention. The median overall treatment time (OTT) was 56 (49‐69) days. Conclusions: This intensive treatment regimen is feasible and safe in locally advanced ESTS, and it achieves oncological results that are comparable with conventional HILP treatment. In addition, the major wound complication risk is comparable and the OTT is reduced.